Relação entre o modelo de gestão de pessoas agency-community com os tipos de vínculos comprometimento e entrincheiramento organizacional - Segala, Viviane (2013)
This work was developed with the purpose of identify the influence of organizational commitment and entrenchment, as well as his relationship with the people management agency-community model. Therefore, we carried out a survey of descriptive character, drawing on quantitative methodologies. The research sample consisted of 268 technical and administrative staff of a Federal Institution of Higher Education, to which was applied a questionnaire from the evaluation model of Organizational Commitment and Entrenchment proposed by Bastos et al (2008) and people management agency-community model proposed by Rousseau and Arthur (1999). Data were analyzed using software "Windows Excel", "SPSS 18" and "SAS 9". Simple correlations descriptive statistics was used the Shapiro-Wilk test and Kruskal-Wallis. We identified positive correlations between the dimensions of commitment and positive correlations between the dimensions of entrenchment. Positive correlations were also found between the people management community model with affective commitment and positive correlations between of people management agency model with normative commitment and entrenchment "Social Position Adjustment" and "Limitation of Alternatives". The results show that the predominant basis of employees is followed by affective instrumental and realize the existence of practices in community management actions in the organization. Despite the agency management practices are not prevalent in the perception of employees, these principles and practices are important when related to personal goals, the concept of self, the need of the employee being seen as an individual with feelings and expectations. Based on the results, one realizes that the Institution has immense significance for the servers, they are interested in her fate and feel proud to tell people that are part of the institution in which they work. The greatest fear of leaving the organization is linked to loss of financial benefits and stability. The survey attributes that a major factor for the dimension of affective commitment identify the strongest bond among the sample studied is how managers think and guide the organization, considering the organizational structure and people. The commitment of people towards the activities they perform; accepting the values of the organization, associated with the implementation of management practices may represent agency and community in the management of UFSM the direction of human effort to achieve the organizational objectives, taking into account the personal objectives, sense of individual and collective responsibilities.